KAJIAN SIFAT FISIK TANAH PADA TANAMAN BAYAM (Amarantus Sp.) DI DESA KALASEY KECAMATAN MANDOLANG KABUPATEN MINAHASA - Melianus Taplo; Joice M. Supit; Sandra E. Pakasi (COCOS, 2018)
ABSTRACT Research has aimed to study the characteristics of physical soil on spinach (Amarantus Sp.) at Kalasey Village, Mandolang Sub-District, Minahasa Regency. Method has use for analysis was tabularis and for sampling was composite than analyzed to the laboratory for some variables such as: soil texture, permeability, and soil water content. Results have shown that the characteristics of physical soil were: texture (silty sand), permeability (rather fast) and the soil water content (well), so that these result were suitable for the growth requirements of spinach. Keywords : Physical Soil and Spinach.